Tsunami Early Warning System Based on Maritime Wireless Communication - Aryanti Karlina Nurendyastuti; Mochamad Mardi Marta Dinata; Arumjeni Mitayani; Muhammad Rizki Purnama; Mohammad Bagus Adityawan; Mohammad Farid; Arno Adi Kuntoro; Widyaningtias (Journal of the Civil Engineering Forum, 2022)
Tsunami buoy, linked to satellite, is commonly used as a tsunami early warning system but has been discovered to have several drawbacks such as the need for approximately 5 minutes to issue an early warning for a tsunami after detecting the initial wave as well as its fragility. It was also reported that the twenty-two buoys placed in the Indonesian seas from 2012 to 2018 were damaged and missing. Therefore, this study proposes a new method for tsunami early warning by integrating ship-to-ship maritime wireless communication. It is important to note that vessels or fishing boats with over 30 GT have the ability to travel more than 100 nmi (approximately 180 km) from the shoreline and can be equipped with point-to-multipoint VHF radio communication. Meanwhile, smaller boats on the fishing ground located approximately 2-5 km from the shore can use a WiFi network to communicate like a wireless mesh while the existing terrestrial network can be used for the ship-to-shore communication between boats and land stations. This system is expected to provide significant benefits for a fishing town such as Pangandaran, West Java, Indonesia which is directly facing Java Megathrust in the Indian Ocean. Therefore, a tsunami numerical simulation was conducted in this study using Shallow Water Equation which involved a hypothetical tsunami simulated from the possible fault source which is approximately 250 km from the source. Moreover, the vessel’s location was assumed to be in line with the fishing ground while the arrival time of the tsunami was estimated from the model to be 22.5 minutes and compared to the relay time of the proposed system which was approximately 5.4 seconds. This is faster in terms of delay than the existing system which relays information through satellite at approximately 5 minutes in an ideal condition and also has the ability to reduce the need for tsunami buoys.